Magnetic and Spin Devices, Volume II - Sverdlov, Viktor; Choi, Seung-bok (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue focuses on topics related to spintronic devices, such as spin-based magnetoresistive memories, multiferroic interconnects and sensors, microfluidic solenoid valves, and magnetoelectric antennas with broad practical applications.